THE PRESENCE OF MOSQUE IN AMBARUKMO PLAZA: WINNING MARKET THROUGH RELIGIOUS CAPITAL - Usman Usman (LIPI Press, 2015)
This article aims to explain the presence of mosque in Ambarukmo Plaza which is categorized one of the leading shopping center in Yogyakarta. The presence of mosque in the shopping center is a unique and interesting phenomenon because the mosque becomes one of the essential elements of the marketing strategy that the management of the mosque is directly under the management of Ambarukmo Plaza. So that the mosque becomes an integral part of the market system which takes place in the shopping center. In view of the business, providing public facilities are part of the service to the consumer. The mosque which is used as a public facility, in addition to having the function as a means of worship, is also functioned as a means of social activities and other activities. In terms of methodology, this article was written by using a qualitative approach that produces descriptive data about the presence of mosque in Ambarukmo Plaza, Yogyakarta. Based on the analysis of field data findings by using Bourdieu’s concepts such practice, habitus, and arena, as well as market and capital, it can be drawn the conclusion that the presence of mosque in the shopping center opens a new space related to the religious capital, and it encourages the owners of religious capital to compete and to win this relatively new arena. Instead, the owner of the economic capital that intentionally creates this new arena is also competing to increase their capital accumulation through the same arena. Thus, the implication, if any shopping center or mall uses the religious capital to win the market, then it will indirectly strengthen the thesis from some social scientists predicted that this is the age of religious resurgence in the public sphere. Keywords: mosque, mall, bourdieu, religious capital and religious resurgence.